Electrical safety in low voltage distribution systems up to 1 000 V a.c. and 1 500 V d.c.. Equipment for testing, measuring or monitoring of protective measures. Effectiveness of residual current devices (RCD) in TT, TN and IT systems Part 6, (16th February 2022) - British Standards Institution,
No abstract available